Impact of high volume GGBS replacement and steel bar length on flexural behaviour of reinforced concrete beams. Issue 1 (March 2021) - Al-Khafaji, Zainab S.; Majdi, Ali; Shubbar, Ali A.; Nasr, Mohammed Salah; Al-Mamoori, Shahad F.; Alkhulaifi, Abdullah; Al-Mufti, Rafal Latif; Al-Rifaie, Ali; Alkhayyat, Ahmed; Hashim, Khalid
Abstract: The Ordinary Portland Cement (OPC) is one of the major ingredient utilized for the manufacture of concrete. The manufacturing of cement includes the release of huge amounts of CO2 gas as a main contributor for greenhouse influence and global warming. Several researchers have investigated the characteristics of OPC concrete utilizing cementitious materials like fly ash, silica fume, and Ground Granulated Blast furnace Slag (GGBS) as replacement materials. The article aims to investigate experimentally the flexural behavior of concrete beams with GGBS. The experimental work was divided into three stages, the first one consists of six reinforced concrete beam specimens with (0%, 40% and 60%) of GGBS. During this stage, the used steel bars were 8 mm diameter and 500 mm in length. In the second stage, the length of the steel bars was reduced to 400 mm with the best mixture of (GGBS+OPC) that obtained from stage 1. In the third stage, the best length of steel bars was used with the best (GGBS+OPC) ratio to be tested at 7, 14 and 28 days from the date of casting. Consequences of this exploration suggests that replacement of OPC with 40 percent GGBS with 500 mm steel bar length can be used in reinforced concrete specimens as it shows comparable results relative to control mixtures (0% GGBS).